The sequential mediation model of students' willingness to continue online learning during the COVID-19 pandemic - Abdul Hafaz Ngah; Nurul Izni Kamalrulzaman; Mohamad Firdaus Halimi Mohamad; Rosyati Abdul Rashid; Nor Omaima Harun; Nur Asma Ariffin; Noor Azuan Abu Osman (The Asia-Pacific Society for Computers in Education (APSCE), 2022)
Abstract This study explored the factors influencing students' willingness to continue with the online learning system during the coronavirus disease 2019 (COVID-19) pandemic by adopting the stimulus-organism-response (SOR) theory. This study also incorporated e-learning readiness, performance, and satisfaction as mediators. The present study employed the purposive sampling method, whereby 2215 data of undergraduate students from a public university were gathered using an online survey and analysed using structural equation modelling (SEM) with Smart Partial Least Squares (SmartPLS). The results revealed that students' e-learning readiness, performance, and satisfaction positively influenced their willingness to continue online learning. Besides, students' e-learning readiness, performance, and satisfaction sequentially mediated the relationship between the online learning system quality and willingness to continue online learning. Significantly, this study provided new insights into the literature on students' willingness to continue online learning by providing empirical evidence on the factors that support their willingness to continue online learning during the COVID-19 pandemic.